Adenocarcinoma of the Colon Disguised as Abdominal Wall Abscess: Case Report and Review of the Literature - Attar, L. (Case Rep Surg, 2018)
INTRODUCTION: Abdominal wall invasion by cancerous cells arising from the colon with an overlying secondary infection that presents as an abdominal wall abscess has been encountered previously, but such a symptom is rarely the first presentation of colon cancer. There are very few cases reported in the literature. CASE PRESENTATION: In this case report, we present a case of a 66-year-old male presenting with abdominal wall abscess that was refractory to treatment. The patient later was found to have an abdominal wall invasion by an underlying colonic carcinoma. CONCLUSION: The purpose of this review is to set forth the proper approach when encountering such cases and emphasize on the significance of keeping a high index of suspicion. We also highlight the need for utilizing proper diagnostic imaging modalities prior to invasive intervention.